1992
DOI: 10.1007/bf00029072
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-dependent biosynthesis of auxins in soil

Abstract: The presence of auxins in soil may have an ecological impact affecting plant growth and development. A rapid and simple colorimetric method was used to assess California soils for their potential to produce auxins upon the addition of L-tryptophan (L-TRP). The auxin content measured by colorimetry was expressed as indole-3-acetic acid (IAA)-equivalents. A substrate (L-TRP) concentration of 5.3 g kg 1, glucose concentration of 6.7 g kg -1, no nitrogen, pH 7.0, 40°C, shaking (aeration) and 48 h incubation time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
3

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(127 citation statements)
references
References 23 publications
2
122
0
3
Order By: Relevance
“…The number of µmol of α-ketobutyrate produced by this reaction was determined by comparing the absorbance at 540 nm (Honma & Shimomura 1978). Auxin production of the selected rhizobacterial isolates as IAA-equivalents in the presence and absence of L-TRP was examined spectrophotometrically by using Salkowski coloring reagent (Sarwar et al 1992). Some pertinent characteristics of the experimental rhizobacteria are shown in Table 2.…”
Section: Characterization Of Isolatesmentioning
confidence: 99%
“…The number of µmol of α-ketobutyrate produced by this reaction was determined by comparing the absorbance at 540 nm (Honma & Shimomura 1978). Auxin production of the selected rhizobacterial isolates as IAA-equivalents in the presence and absence of L-TRP was examined spectrophotometrically by using Salkowski coloring reagent (Sarwar et al 1992). Some pertinent characteristics of the experimental rhizobacteria are shown in Table 2.…”
Section: Characterization Of Isolatesmentioning
confidence: 99%
“…On the other hand, the strain SAW23which was identified as Pseudomonas corrugata produced the lowest auxin value (7.84 mgl -1 ). The differences in the performance of auxin-producing fluorescent pseudomonads may be attributed to the inherent properties of the individual bacteria (Sarwar et al, 1992). Similar results regarding variation in the ability to biosynthesize auxin among fluorescent pseudomonads, many investigators also have reported that auxin production by microbial isolates greatly varied within species and/or strains of the same species (Asghar et al, 2002;Khalid et al, 2004;Ahmed et al, 2005).…”
Section: Phenotypic Characterizationmentioning
confidence: 84%
“…Detection of hydrogen cyanide Production of hydrogen cyanide was detected using the method of (Reddy et al, 2008). Indole acetic acid (IAA) production IAA production by the selected fluorescent pseudomonad was detected qualitatively by the modified method as described by (Brick et al, 1991) and quantitatively in the presence of L-tryptophan (L-TRP) by colorimetric method (Sarwar et al, 1992). Phosphate solubilizing activity…”
Section: Screening and Quantification Of Bacteria For Antagonistic Acmentioning
confidence: 99%
“…The contents of the tubes were then filtered through Whatman No. 2 filter paper and auxin production (indole acetic acid equivalents) was measured colorimeterically at 535 nm as described by Sarwar et al (1992).…”
Section: Methodsmentioning
confidence: 99%
“…The production of plant growth regulators (PGRs) is considered one of the most plausible mechanisms to explain the beneficial effects of Azotobacter Frankenberger, 1991, 1993;Frankenberger and Arshad, 1995;Zahir et al, 1997). The ability of Azotobacter to produce PGRs has been reported and confirmed by various workers (Sarwar et al, 1992;Frankenberger and Arshad, 1995). L-Tryptophan is considered an efficient physiological precursor of auxins in higher plants as well as for microbial biosynthesis of auxins and the possible pathways are well documented in literature (Arshad and Frankenberger, 1997;Frankenberger and Arshad, 1995).…”
Section: Introductionmentioning
confidence: 94%